TEATER ABDUL MULUK DESA SEMBUBUK 1930- 1990 - Ferry Yanto, Endang Mulyani, (Universitas Batanghari Jambi, 2020)
AbstractAbdul Muluk Theater is one of various types and forms of culture in Jambi, especially in Sembubuk Village. But after 1990 the arts no longer had a place in the midst of the community or suffered a setback and did not even appear again. However, on certain occasions this theater was asked to appear by officials of the cultural or tourism service in its form in performances of 17s, cultural or arts festivals. Indeed, its intensity is rarely because of losing paporite by soap operas, step on screens, single organs, or modern theater. Abdul Muluk Theater Sembubuk Village in its appearance underwent several changes, which were originally performed in the form of poems delivered by speaking or reciting until its development was made into a theater performance art performed using a play. Then in terms of place, initially performed at the hall, at home until performed at traditional ceremonies such as marriage ceremonies, circumcision, circumcision and other holidays including; at the 17s, the folk festival was held, and it was filled with TVRI programs.Key words: Change, Abdul Muluk Theater, Semubuk VillageAbstrakTeater Abdul Muluk merupakan salah satu dari berbagai jenis serta bentuk budaya di Jambi, khususnya di Desa Sembubuk. Namun setelah tahun 1990 kesenian tidak lagi mendapat tempat ditengah-tengah masyarakat atau mengalami kemunduran bahkan tidak tampak lagi pertunjukkannya. Namun dalam kesempatan tertentu teater ini diminta untuk tampil oleh pejabat dinas kebudayaan atau pariwisata bentuknya dalam pertunjukan 17an, festival budaya atau kesenian. Memang intensitasnya sudah jarang karna kalah paporit oleh acara sinetron, layar tancap, organ tunggal, atau teater moderen. Teater Abdul Muluk Desa Sembubuk dalam penampilannya mengalami beberapa perubahan-perubahan yaitu awalnya dipertunjukkan berbentuk syair-syair disampaikan dengan cara bertutur atau berpantun hingga pada perkembangannya dijadikan seni pertunjukkan teater dipentaskan menggunakan lakon. Kemudian dari segi tempat, awalnya di pentaskan di balai, dirumah hingga dipertunjukkan pada upacara adat seperti upacara perkawinan, sunatan, khitanan serta perayaan hari besar lainnya diantaranya; pada acara 17an, pegelaran festival rakyat, dan mengisi pada programacara TVRI.Kata kunci: Perubahan, Teater Abdul Muluk Desa Semubuk